Measurement the customer satisfaction towards the service quality at the Suri Delima Restaurant / Muhammad Tarmizie Alias...[et al.] - Alias, Muhammad Tarmizie; Md Salleh, Faridul Atrash; Abd Manaf, Nooraini (2010)
Efficiency and the quality are recognized as the key component of business strategies especially in the restaurant. The concepts of efficiency, while prepared with the capabilities of quality, help the organizations especially restaurant achieve the service effectiveness and excellence. Today’s organizations (restaurant) need to manage continuous improvements and breakthrough in quality that meet customer requirement and expectation. This paper presents the examination of the attributes which influence customer satisfaction towards the service quality at the Suri Delima restaurant. The objectives of this study is to determine the quality the priority of the customers at Suri Delima Anggun Restaurant, to identify customer expectation at Seri Delima Anggun Restaurant, to evaluate customer satisfaction at Seri Delima Anggun Restaurant and to determine relationship between service quality and customers satisfaction. The variables in this study is food and the customers satisfaction and the researcher used the questionnaire as the method to get the information. The research conducted at Suri Delima Anggun Restaurant and the population of the research is the customer of this restaurant. The sample size of the research is 127 respondents and quantitative research methods have been use. Beside that, reliability statistics, descriptive statistics, and Pearson Correlation analysis are use to analyze this research. Based on this research, the researcher fined that food is the most factors that contribute towards customer satisfaction.